Synthesis of dihydrogambirtannine by alkyne [2 + 2 + 2]-cyclotrimerisation - Seankongsuk, Pattarakiat (2025)
The first asymmetric synthesis of (−)-dihydrogambirtannine has been achieved using nucleophilic addition to a chiral sulfinyl imine to establish the stereogenic centre and [2 + 2 + 2] alkyne cyclotrimerisation to construct the aromatic E ring.